Hukum Islam Dan HAM: Tinjauan Hukum Poligami dan Kesetaraan Hak dalam Perkawinan - M Ali Mubarok; Dety Vera Dinyati (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2023)
The Declaration of Human Rights (HAM) in 1948 by the General Assembly of the United Nations (UN) has become a reference for the international community and has influenced aspects of international law. However, the interpretation of human rights and their implementation within the national scope often clashes with local culture and laws. As Islamic law is codified in various Muslim countries which are also part of the United Nations. Is there a conflict between International Human Rights Law and Islamic Law then what is the solution, also how is the harmonization between Islamic Law and Human Rights regarding the permissibility of the practice of polygamy which violates the Principle of Equality is a question that must be answered thoroughly from the perspective of both. The dialogical approach finds answers that are very relevant, through the rule of